A carbon-rich region in Miller Range 091004 and implications for ureilite petrogenesis. (1st February 2017) - Day, James M.D.; Corder, Christopher A.; Cartigny, Pierre; Steele, Andrew; Assayag, Nelly; Rumble, Douglas; Taylor, Lawrence A.
Abstract: Ureilite meteorites are partially melted asteroidal-peridotite residues, or more rarely, cumulates that can contain greater than three weight percent carbon. Here we describe an exceptional C-rich lithology, composed of 34 modal % large (up to 0.8 mm long) crystalline graphite grains, in the Antarctic ureilite meteorite Miller Range (MIL) 091004. This C-rich lithology is embedded within a silicate region composed dominantly of granular olivine with lesser quantities of low-Ca pyroxene, and minor FeNi metal, high-Ca pyroxene, spinel, schreibersite and troilite. Petrological evidence indicates that the graphite was added after formation of the silicate region and melt depletion. Associated with graphite is localized reduction of host olivine (Fo88–89 ) to nearly pure forsterite (Fo99 ), which is associated with FeNi metal grains containing up to 11 wt.% Si. The main silicate region is typical of ureilite composition, with highly siderophile element (HSE) abundances ∼0.3 × chondrite, 187 Os/ 188 Os of 0.1260–0.1262 and Δ 17 O of −0.81 ± 0.16‰. Mineral trace-element analyses reveal that the rare earth elements (REE) and the HSE are controlled by pyroxene and FeNi metal phases in the meteorite, respectively. Modeling of bulk-rock REE and HSE abundances indicates that the main silicate region experienced ∼6% silicate and >50% sulfide melt extraction, which is at the lower end of partial melt removal estimated for ureilites. Miller Range 091004 demonstrates heterogeneous distribution of carbon at centimeter scales and a limited range in Mg/(Mg + Fe) compositions of silicate grain cores, despite significant quantities of carbon. These observations demonstrate that silicate rim reduction was a rapid disequilibrium process, and came after silicate and sulfide melt removal in MIL 091004. The petrography and mineral chemistry of MIL 091004 is permissive of the graphite representing late-stage C-rich melt that pervaded silicates, or carbon that acted as a lubricant during anatexis and impact disruption in the parent body. Positive correlation of Pt/Os ratios with olivine core compositions, but a wide range of oxygen isotope compositions, indicates that ureilites formed from a compositionally heterogeneous parent body that experienced variable sulfide and metal melt-loss that is most pronounced in relatively oxidized ureilites with Δ 17 O between −1.5 and ∼0‰.